2003
DOI: 10.1002/pola.10822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(diethylsiloxane) and its copolymers with different diorganosiloxane units

Abstract: Poly(diethylsiloxane) and its copolymers with various kinds of R 1 R 2 SiO (R 1 ϭ R 2 ϭ methyl or phenyl, or R 1 ϭ methyl and R 2 ϭ phenyl) units have been prepared by the equilibrium polymerization of cyclosiloxanes. All the polymers have been characterized by 1 H and 29 Si NMR, gel permeation chromatography, differential scanning calorimetry (DSC), and dynamic mechanical analysis (DMA) measurements. The results indicate that a random distribution of different units has been obtained in the structures of copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…[6,12,13] The literature provides many examples of this compositional effect. [6,[14][15][16] Surprisingly, the addition of inorganic fillers (such as silica, zinc oxide, iron oxide) is known to accelerate rather than inhibit polymer crystallization, presumably due to fillers acting as nucleating agents. [17] Recently, Zlatanic et al reported the suppression of crystallization in PDMS through inclusion of only 3.6 mol% of statistically distributed diphenylsiloxy (DiPhS) repeating units, or as low as 5 mol% of diethylsiloxy (DiEtS) units.…”
Section: Doi: 101002/macp201800425mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,12,13] The literature provides many examples of this compositional effect. [6,[14][15][16] Surprisingly, the addition of inorganic fillers (such as silica, zinc oxide, iron oxide) is known to accelerate rather than inhibit polymer crystallization, presumably due to fillers acting as nucleating agents. [17] Recently, Zlatanic et al reported the suppression of crystallization in PDMS through inclusion of only 3.6 mol% of statistically distributed diphenylsiloxy (DiPhS) repeating units, or as low as 5 mol% of diethylsiloxy (DiEtS) units.…”
Section: Doi: 101002/macp201800425mentioning
confidence: 99%
“…Thus, crystallization suppression represents an extremely attractive approach for improving low‐temperature properties of polysiloxane elastomers (e.g., for aerospace applications), which extends their application temperature range to their respective T g s. As expected, the introduction of small amounts of randomly placed, irregular repeating units sufficiently introduces asymmetry and effectively reduces crystallizability . The literature provides many examples of this compositional effect . Surprisingly, the addition of inorganic fillers (such as silica, zinc oxide, iron oxide) is known to accelerate rather than inhibit polymer crystallization, presumably due to fillers acting as nucleating agents …”
Section: Introductionmentioning
confidence: 98%
“…Silicone rubbers have been widely used in recent years because of their excellent chemical properties, such as resistance to ozone and weathering, electrical insulating property, and excellent low‐temperature resistance . For example, high‐molecular‐weight poly(diethylsiloxane) (PDES) possesses a low glass transition temperature ( T g ) of −137°C, which is the lowest for any known polymer . However, a rigid crystal forms at temperatures below −73°C, and a conformational disorder in crystals at high temperatures limits the utilization of PDES .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, poly(diethylsiloxane‐ co ‐diphenylsiloxane) and poly(diethylsiloxane‐ co ‐3,3,3‐trifluoropropylmethylsiloxane), as well as poly(diethylsiloxane‐ co ‐ethylphenylsiloxane) and poly(diethylsiloxane‐ co ‐methylphenylsiloxane), have been reported. In addition to the aforementioned copolymers that bear two units, copolymers with three and four units have also been prepared . As mentioned above, whether PDES or PDMS possesses low T g .…”
Section: Introductionmentioning
confidence: 99%
“…The first approach is the synthesis of MESR‐based copolymers. Liu et al synthesized and investigated a series of MESR‐based polymers, including poly(dimethylsiloxane‐ co ‐diethylsiloxane‐ co ‐diphenylsiloxane) and poly(dimethylsiloxane‐ co ‐diethylsiloxane‐ co ‐methylphenylsiloxane). However, random copolymers with high molecular weights are difficult to obtain because comonomers have different reactivities.…”
Section: Introductionmentioning
confidence: 99%